Age at the start of competition and time to top performance in top Japanese athletes: Focusing on differences in competition event and gender - Ikeda, T.; Katsumata, Y.; Suzuki, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2022)
The purpose of this study was to compare the age at which top athletes started the competition, and the age range for advanced athletic activities. 914 athletes and candidate athletes (451 men, 15-51 years old, 463 women, 14-55 years old) who participated in the 2014 Incheon Asian Games were included. In addition, as additional data, the study investigated the ages of 1,971 athletes and candidate athletes at past Olympic Games (Athens 2004, Beijing 2008, London 2012, Rio 2016) (992 men, 979 women). The main results of this study are as follows. 1) There was a significant difference in the age at which the competition started, and both men and women were scoring style (boys: 6.8 ± 3.0 years old, girls: 7.3 ± 2.4 years old) and racket style (boys: 7.2 ± 2.1 years old, girls:: 6.4 ± 1.9 years old), fighting style (boys: 9.2 ± 4.9 years old, girls: 9.0 ± 4.0 years old) and ball game style (boys: 9.2 ± 4.9 years old, girls: 10.2 ± 4.1 years old) are record style (boys: 12.3 ± 5.2 years old, girls: 13.5 ± 6.9 years), target style (boys: 12.6 ± 6.4 years, girls: 14.5 ± 7.7 years) and waterside style (boys: 13.4 ± 3.9 years, girls: 12.1 ± 3.9 years), It showed a low value (P <0.05). 2) There was a significant difference between the competition style in the period from the start of the competition to the participation in the international competition and the winning level in the national competition. ) And record style (6.7 ± 5.0 years) compared to ball game style (9.6 ± 4.4 years) and scoring style (9.9 ± 4.2 years), in girls, target style (4.9 ± 2.2 years) and record style (6.7 ± 4.6 years old) showed lower values than scoring style (7.5 ± 3.9 years old), fighting style (7.7 ± 4.1 years old), racket style (8.2 ± 3.5 years old) and ball game style (8.7 ± 4.0 years old). (P <0.05). 3) For both men and women, there was a significant difference in the age of participation in the Olympics between the competition systems. Compared to waterside style 28.4 ± 4.6 years, target style 30.3 ± 7.1 years and scoring style 31.1 ± 11.6 years, for girls, scoring style 20.7 ± 3.3 years, racket style 23.6 ± 4.4 years, record style 24.2 ± 4.5 years Compared with the age, ball game style 25.4 ± 4.4 years, fighting style 25.8 ± 3.6 years, waterside style 26.5 ± 4.8 years and target style 28.1 ± 6.3 years, the values were lower (P <0.05). From the above, it was suggested that the age at which the competition started, the period from the start of the competition to the top level, and the timing of participation in the Olympic Games may be affected by differences in competition type and gender. To summarize the results of this study, competition systems (scoring style, racket style, fighting style, ball game style) that require more special movements for performance require early competition specialization and longer training period. On the other hand, competition style that require more superiority or inferiority in physical fitness (record style, waterside style) are characterized by specialization in competition at a later time or conversion from another discipline and a shorter training period. These results can be useful basic findings for constructing an athlete training pathway for each sport. In order to build an athlete training pathway, in addition to accumulating further case data of Japanese athletes, it is necessary to compare the play environment, lesson environment, training environment, and successful cases in other countries.